Electrical maintenance - Cook, P (Institution of electrical engineers, 1999)
This is an essential reference book for managers and technicians with responsibilities for electrical aspects of building maintenance. For administrators it provides detailed guidance on their legal responsibilities plus specific guidance (which also applies to electricians) on electrical maintenance.